Role of Digital Marketing in Healthcare Ecosystem - Veda, DV; Sneha, RV; Srivatsala, V (International Journal of Computer Sciences and Engineering, 2025)
Healthcare in today‘s world plays most crucial role in one ‗s life. It is imperative that the information related to health care must reach everyone, to make a healthy and a better world. Digital marketing and branding is a way of imparting information about your product or service through digital medium. Traditional marketing has been replaced largely by digital marketing i.e. ―marketing online‖. This paper discusses how digital marketing is crucial for healthcare in today‘s world. The three main pillars of digital marketing are Content, data and technology. The above three aspects are crucial for healthcare as large amount of data belonging to the consumers/patients are put to use effectively to provide a better service to them. Private corporate healthcare industry and Government healthcare system aim to analyze the above data to devise new health care plans to cater to the patients‘ needs. This paper discusses the technologies and tools pertaining to the digital marketing techniques implemented by healthcare industry. Digital marketing in healthcare is need of the hour in the world of advancing technology.